Fluid strategies and outcomes in patients with acute respiratory distress syndrome, systemic inflammatory response syndrome and sepsis: a protocol for a systematic review and meta-analysis. Issue 1 (December 2015) - Silversides, Jonathan; Ferguson, Andrew; McAuley, Daniel; Blackwood, Bronagh; Marshall, John; Fan, Eddy
Abstract Background Fluid administration to critically ill patients remains the subject of considerable controversy. While intravenous fluid given for resuscitation may be life-saving, a positive fluid balance over time is associated with worse outcomes in critical illness. The aim of this systematic review is to summarise the existing evidence regarding the relationship between fluid administration or balance and clinically important patient outcomes in critical illness. Methods We will search Medline, EMBASE, the Cochrane Central Register of Controlled Trials from 1980 to the present and key conference proceedings from 2009 to the present. We will include studies of critically ill adults and children with acute respiratory distress syndrome (ARDS), sepsis and systemic inflammatory response syndrome (SIRS). We will include randomised controlled trials comparing two or more fluid regimens of different volumes of fluid and observational studies reporting the relationship between volume of fluid administered or fluid balance and outcomes including mortality, lengths of intensive care unit and hospital stay and organ dysfunction. Two independent reviewers will assess articles for eligibility, data extraction and quality appraisal. We will conduct a narrative and/or meta-analysis as appropriate. Discussion While fluid management has been extensively studied and discussed in the critical care literature, no systematic review has attempted to summarise the evidence for post-resuscitation fluid strategies in critical illness. Results of the proposed systematic review will inform practice and the design of future clinical trials. Systematic review registration PROSPERO CRD42013005608. (http://www.crd.york.ac.uk/PROSPERO/ )